Thyrotoxic periodic paralysis in new-onset hyperthyroidism – a case report and review of the literature - Silva Junior, Joaquim Custódio da; Ramos, Helton Estrela (Revista de Ciências Médicas e Biológicas, 2014)
Thyrotoxic periodic paralysis (TPP) is a rare condition related to hyperthyroidism, with specific clinical and physiopathological features. In this article, we discuss a case report of a patient that develops TPP with no previous history of thyroid illness, highlighting semiological characteristics that can help Emergency physicians to suspect of this condition. Subsequently, we review the recent articles about TPP, with focus in the molecular basis of ion channelopathies and predisposing factors, and discuss the therapeutic approach at acute phase of TPP and prevention of crisis recurrence.